Study of compartmentalization in the visna clinical form of small ruminant lentivirus infection in sheep - Ramírez, Hugo (BioMed Central, 2012)
BACKGROUND: A central nervous system (CNS) disease outbreak caused by small ruminant lentiviruses (SRLV) has triggered interest in Spain due to the rapid onset of clinical signs and relevant production losses. In a previous study on this outbreak, the role of LTR in tropism was unclear and env encoded sequences, likely involved in tropism, were not investigated. This study aimed to analyze heterogeneity of SRLV Env regions - TM amino terminal and SU V4, C4 and V5 segments - in order to assess virus compartmentalization in CNS. RESULTS: Eight Visna (neurologically) affected sheep of the outbreak were used. Of the 350 clones obtained after PCR amplification, 142 corresponded to CNS samples (spinal cord and choroid plexus) and the remaining to mammary gland, blood cells, bronchoalveolar lavage cells and/or lung. The diversity of the env sequences from CNS was 11.1-16.1% between animals and 0.35-11.6% within each animal, except in one animal presenting two sequence types (30% diversity) in the CNS (one grouping with those of the outbreak), indicative of CNS virus sequence heterogeneity. Outbreak sequences were of genotype A, clustering per animal and compartmentalizing in the animal tissues. No CNS specific signature patterns were found. CONCLUSIONS: Bayesian approach inferences suggested that proviruses from broncoalveolar lavage cells and peripheral blood mononuclear cells represented the common ancestors (infecting viruses) in the animal and that neuroinvasion in the outbreak involved microevolution after initial infection with an A-type strain. This study demonstrates virus compartmentalization in the CNS and other body tissues in sheep presenting the neurological form of SRLV infection.